Identification and morphology of an apataniid caddisfly larva from the Levant: Apatania cypria Tjeder 1952 - Waringer, Johann; Malicky, Hans (Zootaxa, 2018)
This paper describes the previously unknown larva of Apatania cypria Tjeder 1952. Species association was enabled by the fact that both larval and adult specimens were collected at the same location and that A. cypria is the only apataniid species known from this island (Malicky 2005). Information on the morphology of the larva is given, and the most important diagnostic features are discussed, including those distinguishing it from the closely similar A. subtilis Martynov 1909 and A. theischingerorum Malicky 1981. In the context of the Apataniidae key of Waringer et al. (2015), the three species can be separated by gill arrangement, the number of setae on the metanotal lateral sclerite, and by their distribution patterns: A. cypria is a Levantine species of Cyprus and Lebanon, whereas A. subtilis is restricted to the Caucasus area and A. theischingerorum is a large-scale endemic of the Iberian peninsula.